From Bonus to Onus: Taiwan’s Demographic Transition and Economic Development from 1950 to 2020 - Yeh, Kuang-Ho; Ni, Guihua (Public Governance, Administration and Finances Law Review, 2024)
The driving force behind population change lies in fertility. Over the past 70 years, Taiwan has undergone a fertility transition, rapidly declining from a high peak of natural fertility levels to an ultralow rate. This transition has released a substantial labor force and lead to a significant shift in resource allocation, contributing to rapid economic development in the late 20th century. During the same period, Taiwan’s population aging has progressed faster than that of most countries worldwide. The dependency ratio has negatively impact economic development, making social security an important aspect of resource allocation. The changes in age structure have introduced the concepts of “demographic bonus” and “demographic onus”. As a vibrant economy with a population of over 23 million, Taiwan has enjoyed the demographic bonus for more than a quarter of a century but is now facing the challenges of an aging society and declining fertility rates towards demographic onus. This article examines demographic transitions, economic performance and development in Taiwan from 1950 to 2020, elaborating on the definition, criteria, and quantitative delineation of the demographic bonus and demographic onus. It utilized population and economic statistics for a comparative analysis of the historical evolution, current situation, and prospects of the bonus and onus periods in Taiwan, providing a comprehensive narrative of its historical and empirical developments. Finally, the study underscores the complexity of balancing economic growth with demographic sustainability, emphasizing the necessity for multiple policy adjustments to address the adverse effects of demographic transitions.